2015
DOI: 10.1001/jamapsychiatry.2015.1252
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Representation of Afferent Bodily Signals in Borderline Personality Disorder

Abstract: The ability to perceive and regulate one's own emotions has been tightly linked to the processing of afferent bodily signals (interoception). Thus, disturbed interoception might contribute to the core feature of emotional dysregulation in borderline personality disorder (BPD), as increased levels of depersonalization, body image disturbances, and reduced sensitivity to physical pain suggest poor body awareness in BPD. OBJECTIVE To determine neural correlates of disturbed body awareness in BPD and its associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 76 publications
11
80
1
Order By: Relevance
“…This finding aligns with previous evidence that such alterations correlate with behavioural interoceptive deficits [5,18]. Also, it indicates that difficulties to allocate attention to visceral signals are not confined to psychiatric conditions [67] with diffuse brain abnormalities, and may actually result from relatively circumscribed brain damage. Second, the association of impaired performance with fronto-temporal-insular and fronto-insular damage (in bvFTD and FIS, respectively) corroborates the central role of the IC networks in sensing body states, and of the cingulate and frontal cortices in the integration of interoceptive information [1,2,12].…”
Section: (A) Interoceptive Accuracysupporting
confidence: 90%
See 1 more Smart Citation
“…This finding aligns with previous evidence that such alterations correlate with behavioural interoceptive deficits [5,18]. Also, it indicates that difficulties to allocate attention to visceral signals are not confined to psychiatric conditions [67] with diffuse brain abnormalities, and may actually result from relatively circumscribed brain damage. Second, the association of impaired performance with fronto-temporal-insular and fronto-insular damage (in bvFTD and FIS, respectively) corroborates the central role of the IC networks in sensing body states, and of the cingulate and frontal cortices in the integration of interoceptive information [1,2,12].…”
Section: (A) Interoceptive Accuracysupporting
confidence: 90%
“…Thus, not only does this domain depend on the full integrity of a broad network cutting across anterior and posterior hubs, but it can also be similarly affected irrespective of the underlying physiopathology. This observation, together with evidence of interoceptive accuracy impairments in conditions without a specific locus of brain damage [5,67], confirms the widely distributed and multidimensional nature of its putative mechanisms. In sum, interoceptive accuracy seems to rely on complex interactions among hubs, which span the overall interoceptive network and participate in other functional domains.…”
Section: (A) Interoceptive Accuracysupporting
confidence: 65%
“…Emotion dysregulation may be further improved by interventions that focus on body awareness, such as mindfulness-based therapy, mindfulness-based interventions such as those included in DBT, or dance and movement therapy, the more interoception seems to be impaired in BPD [34]. One might also think of biofeedback interventions that have been shown to promote interoception and emotional state recognition [35] and continue research on neurofeedback as an amendment to psychotherapy.…”
Section: Clinical Implications and Suggestions For Further Researchmentioning
confidence: 99%
“…HEP modulations reflect not only heartbeat perception (Pollatos and Schandry, 2004), but also other processes related to body-brain communication, such as body awareness (Muller et al, 2015), emotional experience (Couto et al, 2015b), motivation (Weitkunat, 1990), attention (Montoya et al, 1993), pain perception (Shao et al, 2011), and stress (Gray et al, 2007). Given these properties, measurements of the HEP may afford critical insights into the cortical monitoring of internal signals, potentially shedding light on two relevant yet underexplored issues: (i) the specificity of internally driven (relative to externally driven) attentional processes; and (ii) its susceptibility to interoceptive training.…”
Section: Introductionmentioning
confidence: 99%
“…Given these properties, measurements of the HEP may afford critical insights into the cortical monitoring of internal signals, potentially shedding light on two relevant yet underexplored issues: (i) the specificity of internally driven (relative to externally driven) attentional processes; and (ii) its susceptibility to interoceptive training. A systematic assessment of such matters could afford valuable normative or reference parameters for clinical research, given that the HEP alterations during interoceptive tasks have been reported in patients with various psychiatric and neurological conditions (Terhaar et al, 2012; Muller et al, 2015; Schulz et al, 2015; García-Cordero et al, 2016). To foster progress in this direction, here we report the first joint assessment of the two abovementioned issues through a combination of behavioral measures, high-density electroencephalography (hd-EEG), and intracranial recordings.…”
Section: Introductionmentioning
confidence: 99%